Implementation of Green Banking and Determinant Factors: Testing the Mediation Effect of Green Financing - Lelly Kartika Sari; Sri Wahyuni; Naelati Tubastuvi; Amir Amir (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
This study examines the effects of bank size, profitability, institutional ownership, and operational efficiency on green banking implementation, with green financing as a mediating variable, using data from nine Islamic commercial banks in Indonesia during 2020–2024. Employing a quantitative approach with path analysis and Sobel tests, the results show that bank size and profitability have a significant positive effect on green financing, while institutional ownership and operational efficiency do not. In the green banking model, bank size and green financing significantly enhance green banking disclosure, whereas profitability, institutional ownership, and operational efficiency exhibit no direct effect. Mediation analysis confirms that green financing significantly mediates the relationships between bank size, profitability, and institutional ownership and green banking, but fails to mediate the effect of operational efficiency. These findings indicate that green financing functions as a critical transmission mechanism linking internal bank characteristics to sustainability disclosure. The study contributes theoretically by extending stakeholder theory through the integration of green financing as a mediating mechanism in Islamic banking, and practically by highlighting that regulatory and managerial efforts should prioritize strengthening green financing capacity, particularly in large and profitable banks, to improve the effectiveness of green banking implementation in Indonesia.